Konsep Pendidikan Islam Dalam Keluarga Menurut Dr. Moh Haitami Salim - Alek Maulana; siti noviah (STIT Sirojul Falah Bogor, 2023)
ABSTRACT The concept of Islamic education in the family according to Dr. Moh. Haitam Salim. Bogor thesis: The concept of Islamic education in the family according to Dr. Moh. Haitami Salim is the title of an independent research that the author conducted with the aim of knowing how the concept of Islamic education in the family, in particular the role of parents in the formation of the personal character of the child. Islamic education is a means of developing knowledge to improve human understanding which includes aspects of faith, worship, morals and others, the teaching and familiarization of praiseworthy attitudes, as well as skills in practice and realization of religious teachings so that humans are able to have strong morals. which are commendable and beneficial to society. In this case, the Islamic education learned in formal education is not enough, because the learning hours in schools are very limited, so in addition to Islamic education in schools, it is necessary to inculcate in the family environment, because the development of the child is the most influential. are family or relatives. The method used in this study uses the library method of study, namely the means and efforts to obtain and test the truth of knowledge from various references according to primary sources. From the different stages of research, it can be concluded that Islamic education in the family is very urgent. The role of parents in informal education is an obligation difficult to deny and give up. Because the most important influence in raising a child since birth may depend on the parenting style of his or her parents. Therefore, the role of parents in education is necessary, especially in the development of character education, where a child must have good character and personality to become a nation of character, of noble character, of responsibility and discipline towards the environment, especially in the educational environment. and society. Thus, Islamic education in the family is formed to maintain the affective values ​​that are instilled in a child in order to achieve educational goals in accordance with Islamic law in order to make a nation of character. Keywords : Islamic Education, Dr. Moh Haitami Salim